Preparation method of aluminum-based liquid injection type drag reduction surface - ZHANG HAIFENG; CHEN WEIPING; LIU XIAOWEI; TUO YANJING (2017)
The invention belongs to the technical field of metal surface treatment and modification and particularly relates to a preparation method of an aluminum-based liquid injection type drag reduction surface. The preparation method comprises the following specific steps: (1) preparing a micron-sized rough surface on an aluminum surface through a chemical etching method; (2) generating a zinc-aluminum oxide thin film through a hydrothermal synthesis method and forming a micro-nano cooperative binary structure on the aluminum surface; (3) modifying with a low-surface energy substance to form a super-hydrophobic surface; (4) injecting lubricating oil into the super-hydrophobic surface to form the injection type drag reduction surface. The prepared injection type drag reduction surface has wetting resistance to water, alcohol, rapeseed oil, industrial white oil and other liquid, a contact angle for the water is about 110 degrees, a sliding angle is less than 3 degrees, and the surface has a good drag reduction effect